Contraction of experimental skin flaps - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1998)
Contraction of experimental skin flaps in loose-skinned animals is a well-known hut underestimated phenomenon that in fact may vary in different circumstances and complicate the calculations of survived and necrosed areas. A standard abdominal island skin flap design in the rat was used in this study to investigate the difference between the contraction rates of necrotic and survived tissues, and to determine its significance in the experimental models. The abdominal island skin flap was based on the inferior epigastric: neurovascular bundles, and it extended from the pubis to the xiphoid and between the both midaxillary lines. The study was conducted in two steps. In the first step, contraction rates of completely necrosed (both pedicles severed) and completely survived (vascular pedicles were intact on both sides either with or without a nerve supply) flaps were assessed in 45 animals. After 1 week, area loss was highly significant in both necrosed and survived flaps (p < 0.001). The rate of contraction was significantly higher in necrosed tissues than in survived tissues (p < 0.001), and it was also significantly higher in the neurovascular flaps than in the denervated flaps (p < 0.05). The contraction of all flaps occurred in the vertical dimension, whereas the horizontal dimension stayed almost the same. In the second step of the study, a unilateral, pedicled abdominal flap was used, which had a constant necrotic zone on the nonpedicled half, either with or without a nerve supply in 30 animals. After 1 week the pedicled halves of all flaps were significantly larger than the nonpedicled halves (p < 0.001). Although the total area loss was higher in the neurovascular flaps than the denervated flaps, the difference was not significant statistically (p > 0.05). There was no statistically significant difference between the areas of necrosis seen in both groups when it was expressed as a proportion of the total flap area (p > 0.05). However, this insignificant difference became significant when the amount of necrosis was expressed as a proportion of only the nonpedicled flap half, favoring the denervated flaps (p < 0.005). It appears in this study that ultimate proportions of surviving and necrosed tissues may be inconsistent owing to the variable contraction rates of these tissues, and misleading conclusions may appear during the assessment of given treatment modalities.
Keywords: ADRENERGIC-NERVES; DELAY PHENOMENON; RAT; DEGENERATION; REGROWTH